THE EFFECT OF HUMAN RESOURCES DEVELOPMENT, COMPENSATION, OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEE PERFORMANCE AT THE REGIONAL OFFICE OF BADAN PERTANAHAN NASIONAL PROVINSI BANTEN - Pancasasti, Ranthy; Ulfasari, Titin Miranti; Utami, Yulistia Herviani; Ghifari, Muhammad Alif; Saepullah, Ahmad (Management Science Research Journal, 2022)
This research will analyze the effect of human resource development, compensation, occupational safety and health on employee performance in the Regional Office of the National Land Agency of Banten Province. Thing that distinguishes this research form previous research is the difference in: (1) the aspects studied, namely aspects of human resource development, compensation, occupational safety and health on the performance of employees at the Regional Office of the National Land Agency of Banten Province, (2) the unit of analysis used in this study, namely the HR of the Regional Office of the National Land Agency, National Land Affair Banten Province. The limitations in this study are only to analyze and calculate the influence of human resource development, compensation, occupational safety and health on employee performance at the Regional Office of the National Land Agency of Banten Province. The population in this study are Regional Office Employees as HR staff at the Land Agency of Banten Province as many as 107 people.The result of this study explain that Human Resource Development, Compensation, and Safety and Health have an significant effect on Employee Performance.